2009
DOI: 10.1038/ismej.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

Gut wall bacteria of earthworms: a natural selection process

Abstract: Earthworms and microorganisms are interdependent and their interactions regulate the biogeochemistry of terrestrial soils. Investigating earthworm-microorganism interactions, we tested the hypothesis that differences in burrowing and feeding habits of anecic and endogeic earthworms are reflected by the existence of ecological group-specific gut wall bacterial communities. Bacterial community was detected using automated ribosomal intergenic spacer analysis of 16S and 23S genes and ribotype data was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(119 citation statements)
references
References 47 publications
7
112
0
Order By: Relevance
“…In fact, although soil is a highly heterogeneous environment where competing species may co-occur at small scales (Amarasekare 2003)-the so-called enigma of soil animal diversity (Anderson 1975)-trait differences between cooccurring anecic earthworm species have been found. In particular, A. longa feeds more extensively on highly mineralized SOM than do Lumbricus spp., the latter showing a stronger preference for fresher detritus (Briones et al 2005;Thakuria et al 2010). Also, the burrowing behaviour of A. longa appears somewhat intermediate between that of endogeic earthworms, which dig transient channels below the soil surface, and true anecic earthworms (Bastardie et al 2005).…”
Section: Do Anecic Earthworm Species Have Similar Effects On Soil Biomentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, although soil is a highly heterogeneous environment where competing species may co-occur at small scales (Amarasekare 2003)-the so-called enigma of soil animal diversity (Anderson 1975)-trait differences between cooccurring anecic earthworm species have been found. In particular, A. longa feeds more extensively on highly mineralized SOM than do Lumbricus spp., the latter showing a stronger preference for fresher detritus (Briones et al 2005;Thakuria et al 2010). Also, the burrowing behaviour of A. longa appears somewhat intermediate between that of endogeic earthworms, which dig transient channels below the soil surface, and true anecic earthworms (Bastardie et al 2005).…”
Section: Do Anecic Earthworm Species Have Similar Effects On Soil Biomentioning
confidence: 97%
“…Also, the burrowing behaviour of A. longa appears somewhat intermediate between that of endogeic earthworms, which dig transient channels below the soil surface, and true anecic earthworms (Bastardie et al 2005). But it should be noted that A. longa and other anecic species are remarkably flexible in their diet (Schmidt 1999;Thakuria et al 2010;Griffith et al 2013), as they tune their behaviour according to environmental conditions (e.g. availability of surface residues).…”
Section: Do Anecic Earthworm Species Have Similar Effects On Soil Biomentioning
confidence: 99%
“…Thakuria et al [25] found that differences in substrate composition can result in microbial shifts of the gut wall-associated bacteria. However, the strongest determinant in the selection process of the gut wall-associated bacteria is the ecological group (anecic or endogeic) followed by the habitat the host occupies and lastly the species of earthworm.…”
Section: Genus-level Differences Between T Tubifexpredated Substratesmentioning
confidence: 99%
“…These microbial changes are probably not only due to the worms' removal or consumption of bacteria and the excretion of degradation products, but also due to the type of substrate the worms consume [25]. In turn, these environmental changes could result in optimised growth conditions for specific bacterial species associated with the worms.…”
Section: Introductionmentioning
confidence: 99%
“…As they are abundant in number and highly productive species, so they are keystone species in the food web of soil environment (Thakuria et al, 2010). Earthworm burrows and drilosphere act as microhabitats for soil invertebrates like nematodes (Andriuzzi et al, 2016), arthropods (Boivin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%